PREVALENCE OF EXHUMATION IN DISTRICT HYDERABAD: A LOCAL EXPERIENCE - Shahla Imran; Lubna Riaz; Farah Waseem; Sadia Abdul Qayyum; Sono Mal; Hanozia Shah (Journal of Ayub Medical College Abbottabad, 2024)
Background: Exhumation of bodies for forensic purposes serves as a pivotal tool in medico-legal investigations, yet there is scant data on the practice within the Pakistani context, particularly in the District of Hyderabad. Aim & Objective were to investigate the prevalence and outcomes of exhumations in Hyderabad, contributing to the knowledge base and understanding the cultural and legal factors influencing post-mortem examinations. Methods: A descriptive, observational, and retrospective analysis of 95 medicolegal exhumations carried out over two years, examining demographic data, the interval between death and exhumation, putrefactive changes, and the determination of the cause of death. Results: Of the 95 exhumations, 58 were male and 37 were female, with the majority of the deceased being under 40 years of age. Nearly half of the exhumations occurred within three months post-mortem, and advanced decomposition was a significant obstacle in determining the cause of death, which remained undetermined in 61.05% of cases. Conclusion: The study revealed a need for timely forensic interventions and highlighted the impact of decomposition on determining the cause of death. It underscores the necessity of advanced forensic methods to improve post-mortem examinations’ outcomes. advance technics are virtual autopsy but we are using old conventional autopsy